Xenophilia and the Religious Openness Hypothesis: Love of the "Stranger" within Religious Fundamentalist and Biblical Foundationalist Ideological Surrounds. Issue 4 (December 2019) - Watson, P. J.; Reagan, Benjamin S.; Chen, Zhuo Job; Morris, Ronald J.
While research documents conservative religious tendencies towards a fear ("phobia") of the stranger ("xeno"), this investigation sought to evaluate possible additional potentials for a love ("philia") of the stranger ("xeno"). Procedures explored a preliminary measure of religious xenophilia that defined xenophilic love and xenophilic grace factors in a sample of 279 American Christian university undergraduates. Xenophilic correlations with religious fundamentalism, biblical foundationalism, social dominance orientation, religious schema, and other religious and psychological constructs uncovered conservative religious potentials for social openness. Partial correlations controlling for biblical foundationalism described a more psychologically closed and less xenophilic religious fundamentalist ideological surround, whereas partial correlations controlling for religious fundamentalism revealed a more psychological open and xenophilic biblical foundationalist surround. These data supported the Religious Openness Hypothesis by confirming the potentials of conservative religious commitments for social as well as for psychological openness.